C-Terminal to Intact Fibroblast Growth Factor 23 Ratio in Relation to Estimated Glomerular Filtration Rate in Elderly Population - Maria Bożentowicz-Wikarek (Kidney & Blood Pressure Research, 2016)
Background/Aims: An analytical equivalence between intact fibroblasts growth factor(iFGF23) and C-terminal(cFGF23) assays is logically expected, however, numerous studies demonstrate lack of a strong association between them. Previously, we have demonstrated the increase in cFGF23 slightly precedes the increase of iFGF23 with the impairment of kidney excretory function; without actually analyzing the ratio between both assays, which are postulated to be affected by declining kidney function. Therefore, the aim of this study was to analyze the ratio between C and iFGF23 in relation to the estimated glomerular filtration rate (eGFR) in an elderly population. Methods: We analysed the variability of c/iFGF23 ratio in the population of 3264 elderly PolSenior study participants (≥ 65years) in the relation to eGFR calculated according full Modification of Diet in Renal Disease, serum levels of C-reactive protein (hs-CRP), and iron. Results: The log10(c/i FGF23 ratio) increased in the subsequent CKD stages. Serum iron and CRP levels reduced the log10 and increased it with age in multivariate regression analysis. Conclusions: Our results suggest impairment in the cleavage of the C-terminal FGF23 fragments with the deterioration of kidney excretory function and age in the elderly population. Inflammation and low serum iron level seems to diminish degradation capacity of FGF23 fragments.